Dinamika Kekerasan dalam Rumah Tangga di Indonesia: Analisis Faktor Penyebab, Dampak Psikologis, dan Upaya Penanganan - Rieldha Meida Aruni; Syarifa Annisa Rahmadani; Wahyuni Pramita; Wulan Rahmadani Saparuddin (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Domestic violence (DV) is a complex social issue that continues to show a high incidence rate in Indonesia. This study aims to examine the contributing factors, psychological impacts, and recovery processes of DV victims through a literature review of 31 scientific articles. The findings indicate that domestic violence is influenced by economic factors, low emotional regulation, past experiences of violence, patriarchal culture, and weak implementation of legal protection. Victims commonly experience anxiety, depression, trauma, decreased psychological well-being, and developmental problems in children. The recovery process is supported by social support, adaptive coping strategies, resilience, and psychological interventions. Integrated efforts across legal, social, and psychological aspects are needed to address domestic violence more effectively.